Patent litigation in Europe - Katrin Cremers; Max Ernicke; Fabian Gaessler; Dietmar Harhoff; Christian Helmers; Luke McDonagh; Paula Schliessler; Nicolas Van Zeebroeck (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We compare patent litigation cases across four European jurisdictions - Germany, France, the Netherlands, and the UK - covering cases filed during the period 2000-2008. For our analysis, we assemble a new dataset that contains detailed information at the case, litigant, and patent level for patent cases filed at the major courts in the four jurisdictions. We find substantial differences across jurisdictions in terms of case loads. Courts in Germany hear by far the largest number of cases in absolute terms, but also when taking country size into account. We also find important between-country differences in terms of outcomes, the share of cases that is appealed, as well as the characteristics of litigants and litigated patents. A considerable number of patents are litigated in multiple jurisdictions, but the majority of patents are subject to litigation only in one of the four jurisdictions.
urn:nbn:de:bsz:180-madoc-347732
Keywords: O34; K11; K41; 330; Patent litigation; Europe